Biodiversity of Soil Fungi of Achanakmar Forest of Bilaspur - Pandey, Pratiksha; Pandey, Bhawana (International Journal of Computer Sciences and Engineering, 2025)
The fertility status of soil depends not only on its chemical and physical composition but also depends of the occurrence of micro-organisms. During the course of study an extensive survey of area of forest of Achanakmar Bilaspur District (Chhattisgarh) was made to investigate the total microbial flora in relation to the seasonal trends in the forest appearance